Analisis pemahaman matematis siswa dalam menyelesaikan soal literasi numerasi ditinjau dari kemampuan awal matematis siswa - Fauzia Hajar Hasanah; Hepsi Nindiasari; Sukirwan Sukirwan (Universitas Sultan Ageng Tirtayasa, 2022)
This qualitative study aims to obtain an overview of students' mathematical understanding in solving numeracy literacy questions in terms of the initial mathematical abilities of students at SMKN 1 Rangkasbitung. The subjects in this study were students of class X Marketing at SMKN 1 Rangkasbitung in the even semester of the 2021/2022 academic year. The subject selection technique used was purposive sampling, which is a sampling technique with certain considerations. The researcher gave an initial ability test in the form of multiple choice and a mathematical understanding test in solving numeracy literacy questions in the form of descriptions, then the selected subjects were communicatively interviewed in conveying their ideas and ideas in solving numeracy literacy questions. The results showed that students who had early mathematical abilities in the high category and were in solving numeracy literacy questions had a relational understanding, while students who had early mathematical abilities in the low category in solving numeracy literacy questions had instrumental understanding.